Gypsy Beliefs in Turkish and Western Literature - Oymak, Alparslan (Rector CIU Cyprus Int Univ, 2021)
Gypsies have been the target of prejudiced approaches in real life and literary works for centuries. The most important of these is their being irreligious and believing in nothing. In the spread of negative opinions about Gypsies in Turkish and Western literature, the share of legends and stories derived from them is at the top. Another reason for the spreading of the bad reputation of Gypsies is that their lifestyle is not seen as suitable for the general structure of the society. There is a widespread perception that they are wild, or rather a threat to civilization, because they do not fit into the city system. Whether they are nomadic or not, Gypsies living in closed groups have been marginalized by the general public and this situation is reflected in the works in the same direction. Although they are depicted with prejudices on issues such as morality, belief, cleanliness and theft in Turkish and Western literature, there arc a considerable number of works that look at Gypsies from within. When all these works arc examined, it is understood that Gypsies have a belief system with strict rules and a deep-rooted tradition, contrary to the common opinion. Marhime beliefs about cleanliness, male and female relationships and taboos about sexuality point to the exact opposite of negative views about them. The belief systems of Gypsies become more comprehensible when their view of life, their perception of time, their attitudes towards death, the importance they give to the family and their use of language are collectively evaluated in the works dealing with Gypsies.
Keywords: Gypsies; Gypsy beliefs; Turkish literature; western literature; marginalisation; Arts & Humanities - Other Topics; Literature